Pengaruh Electronic word of mouth (E-WOM) dan Customer dissatisfaction Terhadap Brand switching Melalui Variety seeking Sebagai Variabel Intervening: Studi pada Konsumen Mixue Kota Padang - Nindy Armelia Putri; Annur Fitri Hayati (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2025)
This study aims to analyze the effect of Electronic word of mouth (E-WOM) and Customer dissatisfaction on Brand switching, and test Variety seeking as an intervening variable for Mixue consumers in Padang City. This type of research is causative, the population in this study is the people of Padang City who have switched brands from Mixue to other ice cream & tea brands in Padang City. The number of samples was determined as many as 100 samples using the Cochran formula and purposive sampling technique. The data used is the type of primary data obtained through distributing questionnaires. The analysis method used is SEM analysis using SmartPLS 4.0 software. The results showed that: 1) E-WOM has a significant effect on brand switching, 2) customer dissatisfaction has a significant effect on brand switching, 3) E-WOM has no significant effect on variety seeking, 4) customer dissatisfaction has a significant effect on variety seeking, 5) variety seeking has a significant effect on brand switching, 6) variety seeking cannot mediate the relationship between E-WOM and brand switching, 7) variety seeking mediates the relationship between customer dissatisfaction and brand switching.